Venom of the Red-Bellied Black Snake Pseudechis porphyriacus Shows Immunosuppressive Potential - Rachael Y. M. Ryan; Viviana P. Lutzky; Volker Herzig; Taylor B. Smallwood; Jeremy Potriquet; Yide Wong; Paul Masci; Martin F. Lavin; Glenn F. King; J. Alejandro Lopez; Maria P. Ikonomopoulou; John J. Miles (Toxins, 2020)
Venoms act with remarkable specificity upon a broad diversity of physiological targets. Venoms are composed of proteins, peptides, and small molecules, providing the foundation for the development of novel therapeutics. This study assessed the effect of venom from the red-bellied black snake (Pseudechis porphyriacus) on human primary leukocytes using bead-based flow cytometry, mixed lymphocyte reaction, and cell viability assays. We show that venom treatment had a significant immunosuppressive effect, inhibiting the secretion of interleukin (IL)-2 and tumor necrosis factor (TNF) from purified human T cells by 90% or greater following stimulation with mitogen (phorbol 12-myristate 13-acetate and ionomycin) or via cluster of differentiation (CD) receptors, CD3/CD28. In contrast, venom treatment did not inhibit TNF or IL-6 release from antigen-presenting cells stimulated with lipopolysaccharide. The reduced cytokine release from T cells was not associated with inhibition of T cell proliferation or reduction of cell viability, consistent with an anti-inflammatory mechanism unrelated to the cell cycle. Deconvolution of the venom using reverse-phase HPLC identified four fractions responsible for the observed immunosuppressive activity. These data suggest that compounds from P. porphyriacus venom may be potential drug leads for T cell-associated conditions such as graft versus host disease, rheumatoid arthritis, and inflammatory bowel disease.